2023
DOI: 10.3389/fgene.2022.1082654
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional gene ZNF281 identified as a molecular biomarker in soft tissue regeneration and pan-cancer progression

Abstract: Regeneration and tumorigenesis are indicated as related processes, while regeneration leads to life and the outcome of tumorigenesis is death. Here, we show the upregulation of zfp281 (zinc finger 281) in our adipose de novo regeneration model through RNA-seq analysis. Then, we validated the upregulation of zfp281 in adipose regeneration via immunofluorescence. Following that, we found that ZNF281 (the human homolog of Zfp281) was upregulated in most types of cancer and related to worse prognosis in 10 tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, researchers have not explored its role in GC. Abnormal ZNF281 expression regulates the Wnt/β-catenin pathway affecting tumorigenesis and progression (Qian et al 2017 ; Zeng, Hou et al 2022 ; Deng, Peng et al 2023 ). 5-FU mediates DNA damage and inhibits DNA damage repair in GC cells through the Wnt pathway, thereby promoting apoptosis and inhibiting proliferation, invasion, and migration (Meng et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, researchers have not explored its role in GC. Abnormal ZNF281 expression regulates the Wnt/β-catenin pathway affecting tumorigenesis and progression (Qian et al 2017 ; Zeng, Hou et al 2022 ; Deng, Peng et al 2023 ). 5-FU mediates DNA damage and inhibits DNA damage repair in GC cells through the Wnt pathway, thereby promoting apoptosis and inhibiting proliferation, invasion, and migration (Meng et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular liver cancer, ZNF281 affects mitochondrial biogenesis through the nuclear respiratory factor 1/peroxisome proliferator-activated receptor gamma co-activator-transcription factor A, mitochondrial axis, triggering cancer progression (Zhao, Zhang et al 2023 ). It has been revealed that ZNF281 involved in regulating immune infiltration in cervical and pancreatic cancers(Hou et al 2022 ). Additionally, low expression of ZNF281 inhibits tumor progression in oral, breast, and cervical cancers (Ji et al 2020 ; Hou et al 2021 ; Starzynska et al 2021 ; Zeng, Hou et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation